Predicting lung dosimetry of inhaled particleborne benzo[a]pyrene using physiologically based pharmacokinetic modeling. (18th September 2016) - Campbell, Jerry; Franzen, Allison; Van Landingham, Cynthia; Lumpkin, Michael; Crowell, Susan; Meredith, Clive; Loccisano, Anne; Gentry, Robinan; Clewell, Harvey
Abstract: Benzo[a]pyrene (BaP) is a by-product of incomplete combustion of fossil fuels and plant/wood products, including tobacco. A physiologically based pharmacokinetic (PBPK) model for BaP for the rat was extended to simulate inhalation exposures to BaP in rats and humans including particle deposition and dissolution of absorbed BaP and renal elimination of 3-hydroxy benzo[a]pyrene (3-OH BaP) in humans. The clearance of particle-associated BaP from lung based on existing data in rats and dogs suggest that the process is bi-phasic. An initial rapid clearance was represented by BaP released from particles followed by a slower first-order clearance that follows particle kinetics. Parameter values for BaP-particle dissociation were estimated using inhalation data from isolated/ventilated/perfused rat lungs and optimized in the extended inhalation model using available rat data. Simulations of acute inhalation exposures in rats identified specific data needs including systemic elimination of BaP metabolites, diffusion-limited transfer rates of BaP from lung tissue to blood and the quantitative role of macrophage-mediated and ciliated clearance mechanisms. The updated BaP model provides very good prediction of the urinary 3-OH BaP concentrations and the relative difference between measured 3-OH BaP in nonsmokers versus smokers. This PBPK model for inhaled BaP is a preliminary tool for quantifying lung BaP dosimetry in rat and humans and was used to prioritize data needs that would provide significant model refinement and robust internal dosimetry capabilities.